2016
DOI: 10.1007/s13238-016-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on MRG701 chromodomain reveal a novel dimerization interface of MRG proteins in green plants

Abstract: MRG proteins are conserved during evolution in fungi, flies, mammals and plants, and they can exhibit diversified functions. The animal MRGs were found to form various complexes to activate gene expression. Plant MRG1/2 and MRG702 were reported to be involved in the regulation of flowering time via binding to H3K36me3-marked flowering genes. Herein, we determined the crystal structure of MRG701 chromodomain (MRG701CD). MRG701CD forms a novel dimerization fold both in crystal and in solution. Moreover, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…For this, we used 8‐day‐old seedlings of the MRG2 pro :: YFP ‐ MRG2 mrg1 mrg2 line, which express the YFP‐MRG2 fusion protein that fully rescues the mrg1 mrg2 mutant phenotype (Bu et al , 2014; Peng et al , 2018). Our anti‐green fluorescent protein (GFP)/yellow fluorescent protein (YFP) IP‐MS analysis identified MRG2 as a binding protein of YFP‐MRG2 (Table S1), which is consistent with previous findings reporting that plant MRG proteins form homodimers (Liu et al , 2016). Interestingly, AtNAP1;1 was also found to be a binding protein of YFP‐MRG2 in the same analysis (Table S1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For this, we used 8‐day‐old seedlings of the MRG2 pro :: YFP ‐ MRG2 mrg1 mrg2 line, which express the YFP‐MRG2 fusion protein that fully rescues the mrg1 mrg2 mutant phenotype (Bu et al , 2014; Peng et al , 2018). Our anti‐green fluorescent protein (GFP)/yellow fluorescent protein (YFP) IP‐MS analysis identified MRG2 as a binding protein of YFP‐MRG2 (Table S1), which is consistent with previous findings reporting that plant MRG proteins form homodimers (Liu et al , 2016). Interestingly, AtNAP1;1 was also found to be a binding protein of YFP‐MRG2 in the same analysis (Table S1).…”
Section: Resultssupporting
confidence: 91%
“…In Arabidopsis, it was found that MRG1/MRG2 and NRP1/NRP2 cooperate together in promoting expression of the key floral repressor gene FLC (present study). Considering that the NRP1 and NRP2, as well as MRG1 and MRG2, form both homodimers and heterodimers (Liu et al , 2016; Zhu et al , 2017), it is reasonable to speculate that they may form a higher order complex of multiprotein components. Previous studies showed that the recruitment of MRG1/MRG2 via binding with CO to FT and via binding with PIF7 to YUCCA8 and IAA9 is required for maintaining chromatin H4K5ac levels at the target genes (Bu et al , 2014; Xu et al , 2014; Peng et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRG1/MRG2 also can form homodimers and heterodimers (Liu et al, 2016). The tethered PIF-MRG multiprotein complex may contribute to function together for the PIF-binding and MRG-binding sites that are separated with variable distances among different target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, changes in pH i have been correlated with cell proliferation [43], differentiation [44], cell cycle progression [45], apoptosis [7] and cancer [46]. In this regard, it is worth noting that His18 of Eaf3 CD is highly conserved (Supplementary Figure S5) and the corresponding histidine of Eaf3 orthologs -namely, His21 in human MRG15, His62 in Arabidopsis MRG2, and His37 in rice MRG701 -actually lies at a structurally equivalent position [47][48][49]. In addition, the interactions between MRG15 CD and methyl-lysine peptides have been found to be strongly sensitive to the pH used for NMR titrations, with little or no interaction between MRG15 CD and H3K36me3 peptide at acidic pH [50].…”
Section: Generality Of the Function Of The Ph I Sensor Activity Of Eamentioning
confidence: 99%